Management - Koontz, Harold; Weihrich, Heinz (New York : McGraw-Hill, 1988)
Part 1 of the book covers the basis of management theory and practice, main contributions to management thought, and the patterns of management analysis. Parts 2 through 6 focus on the managerial functions of planning, organizing, staffing, leading, and controlling. Part 7 discusses challenges in the domestic and international environment, including social responsibility and ethics, as well as comparative and international management. These topics are the basis of the courses on business and society.
Includes bibliographical references and index.
ne 10/07/2019
Loans
Keywords: Management; Industrial management